The role of television in shaping the image of the American soldier at the Iraqi universities (Journal of the College of Basic Education, 2023)
The image has become associated with all aspects of human life at the present time, as he lives inA world permeated and dominated by images, where images fill newspapers, magazines, books, and clothes.billboards, television screens, computers and mobile phones as never before.in human history.The person moves through the images through extended, open and free temporal frameworks.spatial so that he can think and interact with people in far places, bypassing the obstaclesExisting buildings, mountains, seas, etc. The images are linked to memory and imagination.There are differences between the perceptual images and the mental images, that is, between the images of the inside and the images of the outside.Despite the continuous interaction between them, the most prominent of which is that thinking in images goes beyond the limits ofThe direct momentary perceived reality, as it enables one to recall the past and experience it as it is.If it were to happen again by reviewing the pictures and films that are related to it, as he canTo think and visualize the future and to activate and develop his imagination.